Handbook of Personality and Self‐Regulation 2010
DOI: 10.1002/9781444318111.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Delay of Gratification

Abstract: In 1958, the Journal of Abnormal and Social Psychology published a report of experimental research by Walter Mischel. Several aspects of this paper provide clues about what was to come in the next 50 years. It reported focused empirical work using an experimental method to probe seemingly intractable theoretical questions. The research was published in a journal dedicated to abnormal psychology, but the clear message was that delay processes underlying abnormal behavior were on a continuum with typical behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Intuitively, savings could imply future spending (which would be related to materialism), and it seems that, even at this young age, children are able to delay instant gratification related to buying and, rather, save for the future. It would be interesting for future work to systematically explore possible links between materialism, spending and self-regulation strategies and determine whether the children who are savers and better prone to delay spending actually exhibit healthier outcomes, as self-regulation research would appear to suggest (Tobin and Graziano, 2010). Again, it would also be crucial to better understand for what, exactly, children are intending to save their resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively, savings could imply future spending (which would be related to materialism), and it seems that, even at this young age, children are able to delay instant gratification related to buying and, rather, save for the future. It would be interesting for future work to systematically explore possible links between materialism, spending and self-regulation strategies and determine whether the children who are savers and better prone to delay spending actually exhibit healthier outcomes, as self-regulation research would appear to suggest (Tobin and Graziano, 2010). Again, it would also be crucial to better understand for what, exactly, children are intending to save their resources.…”
Section: Discussionmentioning
confidence: 99%
“…Given that children’s self-regulation skills also improve over time, including the ability to delay gratification (Tobin and Graziano, 2010), age could also be related to preferences for saving. Indeed, Belk (1985) reviewed a number of studies with samples spanning childhood through adulthood and found that interest in material possessions declines with age while socially focusing on empathy, equity and sharing increases, which could all be related to children’s preferences to spend resources on others versus themselves.…”
Section: Demographic Considerations and Children’s Spending Preferencesmentioning
confidence: 99%
“…Metcalfe and Mischel (1999) reviewed a host of studies concerning delay of gratification (i.e., resisting the impulse to accept an immediate smaller award in favor of a delayed, but larger one), showing that interference with the “cool, cognitive, 'know' system” resulted in greater reaction to the “hot 'go' system;” that is, choosing the immediate smaller reward (for more recent review, see Tobin & Graziano, 2010). This situation is particularly pertinent to the interrogation-related choice of whether to comply and confess to achieve the short-term goal of escape from the stresses of the interrogation, but with the price of facing the long-term consequences of incrimination, prosecution, and probable incarceration.…”
Section: Impulse Control: Maintaining Priority Of Long-term Goal Purs...mentioning
confidence: 99%
“…Delay of gratification comprises a set of motivational and cognitive mechanisms that lead to larger later rewards as compared to immediate or closer rewards [ 1 , 2 , 3 ]. In this sense, it is intended as a form of regulatory process that involves the ability to control actions and feelings and the implementation of self-control strategies, which are necessary for the execution of difficult-to-achieve intentions [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%